Hexacene generated on passivated silicon. Issue 26 (25th June 2018) - Eisenhut, Frank; Krüger, Justus; Skidin, Dmitry; Nikipar, Seddigheh; Alonso, José M.; Guitián, Enrique; Pérez, Dolores; Ryndyk, Dmitry A.; Peña, Diego; Moresco, Francesca; Cuniberti, Gianaurelio
Abstract : On-surface generation of hexacene by surface-assisted reduction on a H-passivated Si(001) surface. Abstract : On-surface synthesis represents a successful strategy to obtain designed molecular structures on an ultra-clean metal substrate. While metal surfaces are known to favor adsorption, diffusion, and chemical bonding between molecular groups, on-surface synthesis on non-metallic substrates would allow the electrical decoupling of the resulting molecule from the surface, favoring application to electronics and spintronics. Here, we demonstrate the on-surface generation of hexacene by surface-assisted reduction on a H-passivated Si(001) surface. The reaction, observed by scanning tunneling microscopy and spectroscopy, is probably driven by the formation of Si–O complexes at dangling bond defects. Supported by density functional theory calculations, we investigate the interaction of hexacene with the passivated silicon surface, and with single silicon dangling bonds.